Design and Construction of Automatic Clothes Drying Rack Prototype Based on IoT (Internet of Things) - Syahputra, Abdillah; Maulana, Halim (Tsabit Journal of Computer Science, 2024)
During the dry season, the intense heat of the sun is highly sought after by Indonesian communities for various needs, one of which is drying clothes that are still wet. Therefore, Indonesians prefer using clotheslines as a medium for drying clothes. Essentially, in addressing the issue of clotheslines, an automated control system is needed. Advances in the field of science and technology, particularly in IoT (Internet of Things), will lead to new innovations. One such innovation is an automatic clothesline control system, which helps and simplifies human tasks. The system automatically moves or shifts dried clothes to a place that is not exposed to rain. In this research, an automatic clothesline system is designed to secure clothes during rain or other weather changes using several sensors: rain sensor, Light Dependent Resistor (LDR), and Temperature and Humidity Sensor (DHT), as well as an external fan that functions as additional drying assistance during rain. This system utilizes the ESP8266 microcontroller and is based on the Internet of Things, allowing remote monitoring and control via smartphone. Based on conducted tests, this system effectively responds to weather changes.